PRELIMINARY NOTES ON THE DEVELOPMENT OF DDT RESISTANCE IN ANOPHELES CULICIFACIES - A.Zaini; AV.Manouchehri (Tehran University of Medical Sciences, 1973)
Anopheles culicifacies is the vector of malaria in southeastern part of Iran, India, West Pakistan and Ceylon. In 1959 the LC50 % DDT in the Panchmahal district of Gujarat state (India) had increased. DDT resistant population of A. culicifacies has been reported from West Pakistan, Burma and Iran. After application of DDT in 1959, the density of A. culicifacies decreased sharply. The susceptibility test carried out in 1963 showed that the LC50 was 0.5%.After DDT spraying, followed by Dieldrin, for about 10 years the density of A. culicifacies was so negligible that it was not possible to perform susceptibility tests. By April and May of 1973 the density of A.culicifacies in Saidabad, Khairabad and Hit in Baluchesten province, Southeast of Iran, increased to about 500 per shelter. The susceptibility tests carried out showed that A. culicfacies is resistant to DDT and susceptible to Dieldrin and Malathion.